1985
DOI: 10.1111/j.1746-1561.1985.tb04078.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Current School Nurse Practice Activities

Donna H. White

Abstract: In this paper a survey of activities of school nurses will be described. A brief summary of the history of school nursing is included as an introduction to the analysis of the current activities of school nurses. Five current school nurse activity clusters are identified from findings of a study of activities: physical, supportive, educative, administrative, and clerical. The development and implementation of administrative skills are cited as major challenges for school nurses in the 1980s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Activities and the corresponding self-ratings of skill have been correlated using the Pearson r, and meaningful clusters of correlation were identified in the original study. Factor analysis of the data for perceptions of ability in the original study provided good replication of the factor structure, providing some evidence for the validity of the instrument (White, 1985).…”
Section: Methodsmentioning
confidence: 81%
See 3 more Smart Citations
“…Activities and the corresponding self-ratings of skill have been correlated using the Pearson r, and meaningful clusters of correlation were identified in the original study. Factor analysis of the data for perceptions of ability in the original study provided good replication of the factor structure, providing some evidence for the validity of the instrument (White, 1985).…”
Section: Methodsmentioning
confidence: 81%
“…School nurses are incorporating administrative skills into their daily practice. When White (1985) conducted her original study over a decade ago, she saw the challenge for school nurses was to "develop administrative expertise that parallels or supplements their proficiency in the areas of health education, supportive intervention, and physical care" (p. 55). In examining the responses of school nurses employed at both the secondary-and elementary-school level, the current study found nurses practicing in all the arenas of school nursing practice: physical care, supportive care, education, and administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the role of the school nurse was health supervisor, direct care provider, health counselor, and health educator. White ( 1985) presented a study of school nurses that found most of school nurse practice time was spent in assessment and providing care for students. A comparison of students', parents', and teachers' perceptions of the school nurse revealed that providing emergency care was ranked as most important by all three groups (Nehls, 1989).…”
Section: Review Of Literaturementioning
confidence: 99%